The correlation between health status and quality of life in southern Brazil - Zubaran, Carlos; Persch, Karin; Tarso, Desire; Ioppi, Ana; Mezzich, Juan (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: The interconnections between quality of life and health status as assessed via questionnaires have not been thoroughly investigated. The objective of this study was to investigate a possible correlation between the constructs of general health status and quality of life as assessed by the Portuguese versions of two questionnaires recently adapted and tested in Brazil. DESIGN AND SETTING: This was a cross-sectional study in which two self-administered questionnaires were used. This investigation was conducted at healthcare services associated with the Universidade de Caxias do Sul, Brazil. METHODS: This study presents data from a sample of 120 volunteers who completed the Portuguese versions of the Personal Health Scale and the Multicultural Quality of Life Index questionnaires. Bivariate linear regression analysis and Pearson correlation coeffi cients were generated from the scores of the two questionnaires. RESULTS: A signifi cant correlation between the concepts of quality of life and health status as evaluated by the Portuguese versions of both questionnaires was observed. Almost all of the health-related questions displayed strong correlations with the overall concept of quality of life. The magnitude of this correlation accounted for almost half of the observed variance. CONCLUSIONS: These fi ndings indicate that, within this sample, health-related issues were key factors for the overall experience of wellbeing and quality of life. The similarities observed across the different groups indicate that the interrelation between health status and quality of life was homogenous, regardless of presence and/or type of ailments.